How Poor Leadership Skills Elicit Unethical Behavior: Evidence from Public Organizations - Abderrahmane Benlahcene; Houcine Meddour (Jurnal Studi Pemerintahan)
Global political and financial entities have witnessed many scandals linked to leaders’ unethical behavior. Previous research suggests that the susceptibility of leaders to act in an unethical way is rooted in various individual, organizational, and social factors. However, unethical leadership is scarcely examined in the context of African countries. This study explores the role of poor leadership skills and qualities in eliciting unethical leadership behavior in Algerian public organizations. Using an exploratory qualitative approach, 15 leaders and managers were included in series of in-depth interviews. The results of the data analysis revealed that poor leadership skills and competencies are critical antecedents of unethical leadership behavior within Algerian public organizations. This study contributes to the ongoing research efforts that seek to identify and minimize the causes of unethical behaviors of leaders across sectors and disciplines. This study provides insights into the construct of unethical leadership and how individual, organizational, and social factors predict leaders’ unethical behavior. While there are many studies on the issue of unethical leadership, research on the potential role of poor leadership skills in eliciting unethical behavior is scarce, especially in Algeria. This study found that there is a strong link between skills and competencies of leaders and their ethical behavior within organizational settings.